2002
DOI: 10.5858/2002-126-0157-lwphe
|View full text |Cite
|
Sign up to set email alerts
|

Livebirths With Placental Hemorrhagic Endovasculitis

Abstract: Background and Objective.—Hemorrhagic endovasculitis (HEV) is a vasodisruptive alteration of fetal-placental blood vessels that has been associated with perinatal morbidity and mortality and abnormalities of growth and development. Clinicopathologic conditions that are often identified in pregnancies with HEV-affected placentas include villitis of unknown etiology, chorionic vessel thrombi, villous erythroblastosis, meconium staining, and maternal hypertension. The clinical implications of HEV are often disput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The result of the present study is comparable to Melamed N et al's [20] study, which shows perinatal outcome was more severe in cases of oligohydramnios complicated by PIH than in isolated oligohydramnios. So, a woman who is at term with isolated oligohydramnios with reassuring fetal surveillance and absence of maternal morbidity and evidence of IUGR is not associated with adverse perinatal outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…The result of the present study is comparable to Melamed N et al's [20] study, which shows perinatal outcome was more severe in cases of oligohydramnios complicated by PIH than in isolated oligohydramnios. So, a woman who is at term with isolated oligohydramnios with reassuring fetal surveillance and absence of maternal morbidity and evidence of IUGR is not associated with adverse perinatal outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown associations between VUE and placental pathologies such as fetal vascular malperfusion and chronic deciduitis. [16][17][18] Other authors have reported associations between VUE and umbilical cord abnormalities such as marginal cord insertion and cord hypercoiling. 19,20 Despite the associations, studies of clinical risk factors associated with VUE are still needed, especially those with larger sample sizes to increase generalizability.…”
mentioning
confidence: 99%